A qualitative study exploring individuals' experiences living with dysvascular lower limb amputation. Issue 10 (8th May 2022) - MacKay, Crystal; Cimino, Stephanie R.; Guilcher, Sara J. T.; Mayo, Amanda L.; Devlin, Michael; Dilkas, Steven; Payne, Michael W.; Viana, Ricardo; Hitzig, Sander L.
Abstract: Purpose: The majority of lower extremity amputations (LEAs) are the result of diabetes or peripheral vascular disease. There is a paucity of literature on individuals' experiences living with dysvascular LEAs in the community, particularly in Canada. The purpose of this study was to explore the perceptions and experiences of community-dwelling adults living with dysvascular LEA. Methods: Semi-structured qualitative interviews were conducted with individuals with a dysvascular LEA recruited from three rehabilitation hospitals. Participants were included if they were English-speaking adults at least three months post-amputation and no longer receiving inpatient rehabilitation. Sampling was purposive to ensure variation by gender, level of amputation, and geographic location. Data were analyzed using an inductive content-analysis approach. Results: Thirty-five interviews were completed with individuals with dysvascular LEA. Study participants portrayed LEA as having an impact on many aspects of their lives, resulting in changes in their mobility, social activities and roles, and psychological wellbeing. Three main factors shaped individuals' experiences with dysvascular LEA including social support, accessibility, and socioeconomic factors. Conclusion: Our findings highlight the impacts of dysvascular LEA in peoples' lives. Future research is warranted to explore how community-based interventions and strategies can address the ongoing needs of individuals with dysvascular LEA. Implications for rehabilitation: Our findings highlight the long-term impacts of dysvascular lower extremity amputations, which resulted in changes in mobility, social activities and roles, and psychological wellbeing. Participants identified issues in access to community services and resources, including rehabilitation. Mechanisms to identify people at risk for social isolation need to be developed and implemented in rehabilitation centers. Access to ongoing rehabilitation services in the community are needed to optimize mobility outcomes and address ongoing psychological needs.